Penerapan Tata Bahasa Indonesia dalam Manajemen Perkantoran untuk Meningkatkan Profesionalisme - Apriliana, Anisa Dea; Arifin, Aqiila Nurunnisa; Fauzan, Are Lingga; Nadhifa, Athiya Putri; Rahma, Aulya; Rahmah, Azkia; Rizkiyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
The use of proper Indonesian grammar in office management plays a crucial role in supporting professionalism and the effectiveness of internal and external communication within an organization. This research aims to identify common forms of linguistic errors found in office administrative documents, such as errors in the use of capital letters, separation of the prefix 'di', word choice, and the incorrect use of punctuation marks according to the rules. The research employs a descriptive qualitative method with literature study techniques, supplemented by documentation of several examples of official letters and interviews with office administrative staff to obtain empirical data. The collected data was analyzed qualitatively through a process of classifying types of errors, interpreting contexts, and studying the impact of linguistic errors on the image of professionalism. The research results show that grammatical errors can lower the credibility and professional impression of the institution. Conversely, the application of correct grammar improves information clarity, communication efficiency, and strengthens the institution's image. Therefore, this study recommends the importance of structured Indonesian grammar training and the establishment of an internal editing team as a strategy to improve the quality of official documents in the office work environment